Ingestion and effects of polystyrene nanoparticles in the silkworm Bombyx mori. (October 2020) - Parenti, C.C.; Binelli, A.; Caccia, S.; Della Torre, C.; Magni, S.; Pirovano, G.; Casartelli, M.
Abstract: Information on the occurrence and effects of nanoplastics in ecosystems worldwide currently represent one of the main challenges from the ecotoxicological point of view. This is particularly true for terrestrial environments, in which nanoplastics are released directly by human activities or derive from the fragmentation of larger plastic items incorrectly disposed. Since insects can represent a target for these emerging contaminants in land-based community, the aim of this study was the evaluation of ingestion of 0.5 μm polystyrene nanoplastics and their effects in silkworm ( Bombyx mori ) larvae, a useful and well-studied insect model. The ingestion of nanoplastics, the possible infiltration in the tissues and organ accumulation were checked by confocal microscopy, while we evaluated the effects due to the administered nanoplastics through a multi-tier approach based on insect development and behaviour assessment, as endpoints at organism level, and the measurements of some biochemical responses associated with the imbalance of the redox status (superoxide dismutase, catalase, glutathione s-transferase, reactive oxygen species evaluation, lipid peroxidation) to investigate the cellular and molecular effects. We observed the presence of microplastics in the intestinal lumen, but also inside the larvae, specifically into the midgut epithelium, the Malpighian tubules and in the haemocytes. The behavioural observations revealed a significant (p < 0.05) increase of erratic movements and chemotaxis defects, potentially reflecting negative indirect effects on B. mori survival and fitness, while neither effect on insect development nor redox status imbalance were measured, with the exception of the significant (p < 0.05) inhibition of superoxide dismutase activity. Graphical abstract: Image 1 Highlights: First study on nanoplastic uptake and effects in the silkworm Bombyx mori . Presence of nanoplastics in tissues and haemolymph. Nanoplastic ingestion alters larval locomotor behaviour.